ANALISIS PENERAPAN UU NO.22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN (Studi Putusan No. 45/Pid.Sus/2015/PN Skt.) - NUGROHO, DANANG ANDY (Dinamika Hukum, 2016)
The purpose of this study is to assess the consideration of the judge in Decision No. 45/ Pid.Sus/2015/ PN Skt and examine considerations associated with the goal judge LLAJ Act. The background is that in which the object UULAJ one of which was the establishment of the rule of law and legal certainty for the public. In this case study will be conducted in the judge's decision crimes related to violations of the provisions of Article 310 paragraph (4) of Law No. 22 Year 2009 regarding Traffic and Road Transportation. The research method consists of the type of normative juridical research, the nature of descriptive research, data and data sources consisting of primary and secondary legal materials in the form of legislation and the judge's decision. Data collection is done by identifying positive law, and with study literature by reading a variety of literature relating to the problems examined. Normative data were analyzed qualitatively. The results showed that the considerations that led to the decision begins with consideration concerning the events that constitute a legal fact. Next is consideration of their juridical aspects that form the fulfillment of the elements of a criminal offense under Article 310 paragraph (4) UULAJ, namely elements: whoever is driving a motor vehicle; due to negligence has caused a traffic accident; lead others died. But beyond that it is not readily apparent juridical considerations relating to the sociological aspect of the problem is mainly associated with the effect of its decision for the community at large. In consideration of the reasons the judge does not appear related to the length of criminal will punished. Related with UULAJ purpose is merely fulfill the purpose of law enforcement and legal certainty, namely that those who violate UULAJ subject to criminal sanctions. In terms of the ruling, especially the length of sentence imposed by the judge to the defendant there is a considerable gap sharply between threatened is for 6 (six) years, with the significantly imposed by the judge is imprisonment for six (6) months deducted for the defendant to be in custody. Although this is the authority of the judges in accordance with freedom and conviction, but from the standpoint of the objective of sentencing, it is the impact on others lack the deterrence effect, meaning that the learning has not been able to provide for the public to be careful in the pass-traffic. Keyword : Application of Law No. 22 In 2009, Decision No. 45/ Pid.Sus/ 2015 / PN Skt.